Median nerve T2 assessment in the wrist joints: Preliminary study in patients with carpal tunnel syndrome and healthy volunteers. Issue 4 (7th November 2013) - Cha, Jang Gyu; Han, Jong Kyu; Im, Soo Bin; Kang, Sung Jin
<x xml:space="preserve">Abstract</x> Purpose To perform a prospective quantitative analysis of median nerve T2 values and cross‐sectional area (CSA) in patients with carpal tunnel syndrome (CTS) as compared to asymptomatic volunteers. Materials and Methods Twelve CTS patients with positive nerve conduction results and 12 healthy volunteers (controls) were enrolled and underwent axial T2 mapping of the wrist joints. Median nerve T2 values and CSAs at the distal radioulnar joint, pisiform, and hook of hamate levels were compared between the groups. Results The T2 values at the proximal and distal carpal tunnel were higher in the CTS patients than in the controls (P < 0.05). The T2 values at the distal radioulnar joint did not differ between the groups (P = 0.99). The CSAs of the median nerve at all levels of the carpal tunnel were significantly larger in the CTS patients than in the controls (P < 0.05). Conclusion In conclusion, our study demonstrated that median nerve T2 assessment is feasible and that T2 assessment may offer functional information about the median nerve in the carpal tunnel and has the potential to be a promising complementary method for evaluation of CTS patients. A future study with larger sample sizes is necessary to investigate the potential effect of median nerve T2 assessment to a reliable tool in the diagnosis of CTS.J. Magn. Reson. Imaging 2014;40:789–795 © 2013 Wiley Periodicals, Inc.